Research Note: SOCS2 contributes to reduction of the third digit during development of the chicken forelimb - Xiaoping Li; Shanshan Li; Shibin Bai; Yining Tang; Ziqiu Jia; Jialong Yin; Xiaona Xu; Junpeng Zhang; David M. Irwin; Shuyi Zhang; Zhe Wang (Poultry Science, 2024)
ABSTRACT: The development of the avian wing pattern has been the subject of heated debate due to its special shape. The Suppressor of cytokine signaling 2 (SOCS2) gene encodes a negative regulator of growth hormone (GH) signaling and bone growth and is known to be strongly expressed in the third digit of chicken forelimbs. These observations suggest that SOCS2 might regulate the morphology of the avian wing, however, the function of SOCS2 in avian limb development remains unknown. Here, we reexamined SOCS2 expression in successive developmental stages of chicken limb development by in situ hybridization (ISH) and describe extended expression from the posterior of the stypolod to the third digit of the forelimbs. We used the RCAS avian retrovirus to overexpress SOCS2 in the developing chicken limb buds, which resulted in reduced or malformed chicken wings while hindlimbs developed normally. Transcriptome sequencing (mRNA-Seq) revealed changes in expression of genes known to be associated with growth and development in forelimbs with overexpressed SOCS2. This study highlights a pivotal role for SOCS2 during the development of the wing in the chicken and provides new insight into molecular mechanisms regulating avian limb development.